The Influence of Brand Activism on Consumer Purchase Intention Through Brand Trust and Brand Image of The Body Shop Products After Change of Ownership in Bandung City - Arinda Yoseffira; Abdul Ahmad Hafidh Nurmansyah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The change in ownership of The Body Shop has the potential to influence consumer perceptions of the brand's social commitment, which has long been known through brand activism. This study aims to analyze the influence of brand activism on purchase intention through brand trust and brand image for The Body Shop products after the change in ownership in Bandung City. This study used a quantitative method with a survey approach. The sample was determined using a purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using regression analysis and the Sobel test. The results showed that brand activism had a positive and significant effect on brand trust and brand image. In addition, brand trust and brand image also had a positive and significant effect on purchase intention. Both variables were proven to mediate the influence of brand activism on purchase intention. These findings indicate that positively perceived brand social activities can increase trust, strengthen brand image, and encourage consumer purchase intention.